The Influence of Product Quality, Price and Exchange Rate towards Export Volume On SME’s Creative Sculpture Industry in Mojokerto - Setia Pratama, Ade; Sudarmiatin, Sudarmiatin (Publisher Cv. Inara, 2025)
The aim of carrying out this research is to determine the influence of production concepts, prices and exchange rates on the export volume of the creative sculpture craft industry in Mojokerto, East Java, Indonesia. Research includes research with a quantitative approach. Primary data was collected using a questionnaire during the period February 2025. Based on the data that was collected, the total amount of data that can be used is sixty SME’s. The results show a simultaneous influence, the three independent variables used jointly influence the dependent variable. Partially, it was found that production did not have a significant influence, while international prices and exchange rates had a significant influence. It is hoped that the results of this data processing will have implications for creative sculpture industry producers in Indonesia in general to be able to improve quality in order to increase export volume so that it has a significant impact on economic growth and social welfare.